2012 4th International Workshop on Hot Topics in Software Upgrades (HotSWUp) 2012
DOI: 10.1109/hotswup.2012.6226611
|View full text |Cite
|
Sign up to set email alerts
|

How to have your cake and eat it too: Dynamic software updating with just-in-time overhead

Abstract: Abstract-We consider the overhead incurred by programs that can be updated dynamically and argue that, in general, and regardless of the mechanism used, the program must incur an overhead during normal execution. We argue that the overhead during normal execution of the updateable program need not be as high as the overhead for the updated program. In light of the fundamental limitations and the differences in the overhead that must be incurred by the updateable and updated programs, we propose a new mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Also, number of authors have highlighted additional DSU approaches including dynamic replacement [22, 54, 66, 75, 86, 92, 93 ], dynamic instrumentation [52, 59, 60, 74, 84, 94 ], dynamic linking [37, 39, 53, 75, 83, 85 ], lust‐in‐time compilation [30, 44, 55, 58, 76, 95 ], wrapper [4, 40, 42, 44, 52 ], dynamic aspect‐oriented [35, 41, 50, 96, 97 ], extension of features [98, 99 ], dynamic adaptation [43, 59 ], rolling update [84 ], object transformer [49 ], data‐driven programming [92 ], distributed DSU [38 ], dynamic core library update [56 ], using run time to support DSU [92 ], procedure‐oriented [30 ], micro‐language‐based [100 ], and dynamic rebinding [5 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, number of authors have highlighted additional DSU approaches including dynamic replacement [22, 54, 66, 75, 86, 92, 93 ], dynamic instrumentation [52, 59, 60, 74, 84, 94 ], dynamic linking [37, 39, 53, 75, 83, 85 ], lust‐in‐time compilation [30, 44, 55, 58, 76, 95 ], wrapper [4, 40, 42, 44, 52 ], dynamic aspect‐oriented [35, 41, 50, 96, 97 ], extension of features [98, 99 ], dynamic adaptation [43, 59 ], rolling update [84 ], object transformer [49 ], data‐driven programming [92 ], distributed DSU [38 ], dynamic core library update [56 ], using run time to support DSU [92 ], procedure‐oriented [30 ], micro‐language‐based [100 ], and dynamic rebinding [5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Current techniques to define statesA number of studies have demonstrated 12 techniques to define states in DSU including state transformer [45, 73, 83, 95, 115 ], formalise as state machine [9, 61, 83, 120 ], adaptation [41, 65 ], prepare ready tainted states [101 ], state convergence algorithm [126 ], state‐based specification language [83 ], enforcing restrictions [116 ], model checkers [83 ], using check points [37 ], custom state transfer [116 ], convert states bi‐directionally [42 ], and event‐based [66 ]. C. Existing techniques to transfer states in DSUBefore we list the identified states transformations techniques, it is interesting to mention number of techniques utilised in DSU to assist in states transformations in the selected primary studies, the techniques are including wrappers [16, 22, 43, 46, 52, 77, 94, 95 ], adaptation [4, 38, 41, 43, 59, 100, 129 ], refactoring [47, 50, 55, 74, 86, 99, 123 ], proxies [41, 46, 53, 113, 119, 131 ], class loaders [55, 85, 86, 123 ], in‐Place Proxification [43, 55, 91 ], adjustment [41, …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations